Destroying Blackness One Body At A Time: Examining The Mediated Representations Of Lynchings Past And Present - Nelson, Bethany Callan (2015)
This thesis explores the politics of racial violence in America. Lynchings have served as a means for controlling black communities since the end of the Civil War. For southerners, the model of the plantation economy had to be followed during industrialization in order to maintain social and economic hierarchies. This paper examines numerous aspects of lynchings and their legal justifications as foundational to modern police and vigilante killings. A critical race virtual ethnography was conducted to explore the similarities and differences between historical lynchings and the recent killings of black men in the media. I have outlined that there are many problematic similarities between historical and recent killings that highlight the racial violence that has plagued the United States. By looking specifically at two notable cases, Trayvon Martin and Michael Brown, a deeper insight can be gained into modern racial violence and its implications